Microencapsulation Efficiency of DCOIT Biocide in the TPM/SiO2 System and a Study of Their Acute Toxicity - Assem Issayeva; Saule Aidarova; Galiya Madybekova; Seitzhan Turganbay; Alpamys Babayev; Miras Issakhov; Altynay Sharipova; Reinhard Miller; Botagoz Mutaliyeva (Colloids and Interfaces)
Biocides are often used in various industries and applications to control microbial growth and prevent the deterioration of materials, and they often have the ability to target a wide range of microorganisms rather than being specific to one type. They are designed to be highly effective at killing or inhibiting the growth of microorganisms and some biocides have residual activity, meaning they remain active for a period of time after application, providing longer-term protection. Biocides need to be compatible with the materials and surfaces they are applied to without causing damage or adverse effects, and they should remain stable under various environmental conditions, such as temperature and pH, to maintain their efficacy over time. In this study, microcapsules incorporating the biocide 4,5-dichloro-2-n-octyl-4-isotriazolin-3-one (DCOIT) were synthesized, and their effectiveness was evaluated. The investigation focused on several aspects, including colloidal chemical properties such as interfacial tension at pH values of 3, 7, and 9, as well as the size, ζ-potential, and morphology of the microcapsules. To validate the microcapsule production, elemental analysis was performed, and the effects on wettability and toxicological properties were assessed within the DCOIT + trimethoxysilyl propylmethacrylate/silicon dioxide nanoparticle system. Interfacial tension kinetics were measured using the PAT-1 tensiometer. The microcapsules exhibited an average diameter of 146 ± 1 nm following emulsification, with a ζ-potential of −50.2 ± 1 mV, as determined by the Malvern Zetasizer Nano Z. The morphology of the microcapsules was characterized using the SEM Controller 1550. Elemental composition was analyzed via energy-dispersive X-ray microanalysis (EDAX). The study concluded that the DCOIT biocide, when incorporated in the TPM/SiO2 system, demonstrated non-toxic properties.